2020
DOI: 10.18231/j.ijogr.2020.055
|View full text |Cite
|
Sign up to set email alerts
|

A case series on maternal and neonatal outcomes of hydrotherapy during labor and childbirth

Abstract: Hydrotherapy, is also called as aquatic or water therapy, and its benefits include improved muscle strength and endurance, increased joint range of motion and enhanced cardio respiratory functioning and reduced cardio metabolic risk profile. Utilization of hydrotherapy during labor and child birth is increasing globally among the educated public. Despite its exclusive benefits, data on its safety and outcomes are still lacking especially in India. Hence it is the need of the hour for the clinicians to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This study observed that no difference was seen between the hydrotherapy and control groups in terms of blood loss amounts and postpartum Hb and Hct levels. These findings are similar to the results of the studies by Gautham and Devi (2020) and Zhang and Yang (2022). Contrary to our study, two studies found that water immersion was effective in reducing postpartum haemorrhage (Burns et al, 2022; Cristina et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study observed that no difference was seen between the hydrotherapy and control groups in terms of blood loss amounts and postpartum Hb and Hct levels. These findings are similar to the results of the studies by Gautham and Devi (2020) and Zhang and Yang (2022). Contrary to our study, two studies found that water immersion was effective in reducing postpartum haemorrhage (Burns et al, 2022; Cristina et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…fourth-degree lacerations between water and land birth groups while increasing the rate of first-and second-degree tears. There are however various other studies with contrary reports (Dahlen et al, 2013;Gautham & Devi, 2020). These inconsistent results for the effect of hydrotherapy on perineal outcomes may be related to differences in study samples' age, parity, intrapartum care and the follow-up methods used.…”
Section: The Effect Of Hydrotherapy On Maternal Health Outcomesmentioning
confidence: 94%